Efficient organic photomemory with photography-ready programming speed - Kim, Mincheol (Sci Rep, 2016)
We propose a device architecture for a transistor-type organic photomemory that can be programmed fast enough for use in electrical photography. Following the strategies used in a flash memory where an isolated charge storage node or floating gate is employed, the proposed organic photomemory adopts an isolated photo-absorption zone that is embedded between upper and lower insulator layers without directly interfacing with a semiconductor channel layer. This isolated photo-absorption zone then allows the device to operate in electrically ‘on’ state, in which the high electric-field region can have a maximal spatial overlap with the illuminated area for efficient and facile light-programming. With the proposed approach, a significant threshold voltage shift is attained even with the exposure time as short as 5 ms. High quality dielectric layers prepared by initiated chemical vapor deposition ensure erasing to occur only with electrical signal in a controlled manner. Retention time up to 700 s is demonstrated.